Filling the gaps sustainably: an island case study of rural dental workforce challenges - Bettiol, Silvana; Naresh, Arish; Khan, Shahrukh (Frontiers in Dental Medicine, 2025)
Tasmania faces ongoing challenges in providing equitable oral health care across its geographically dispersed and ageing population. Tasmania has the lowest dental practitioner-to-population ratio in Australia, alongside long wait times and limited access to care in rural and regional areas. This perspective explores the demographic and workforce distribution trends that influence oral health service delivery in Tasmania using Census data, regulatory records, and key public sector audits. We highlight critical gaps in service provision and policy, reflect on the implications of the workforce maldistribution, argue for expanding the oral health therapy workforce and explore the transdisciplinary approaches currently implemented that prioritise sustainable, community-integrated oral health care. Such models align with the United Nations Sustainable Development Goals (SDGs), particularly SDG 3 (Good Health and Well-being), but also encompass SDGs 4, 5, 6, 8, 9, 10, 13 and 17, which respond to environmental and social contexts. This perspective highlights the intersections of planetary health, oral health, and community well-being, arguing that sustainable, health-centred solutions must address both human and environmental health outcomes.